Solubilization capacity of surfactant due to its different chain length of lipophile and hydrophile - Marchaban . (Indonesian Journal of Pharmacy, 2005)
The aim of the study is to look at the influence of different chain length of hydrophile and lipophile of the surfactants to their solubilization capacity. The solubilization capacity of surfactants with different chain lengths of lipophile and hydrophile has been performed by preparing somesolubilization form formulas, using several kinds of lipophilic chain length, i.e. cetyl (C-16), stearyl (C-18), and oleyl (C=18 with unsaturated chain) alcohols and ethyleneoxyde chain length of 2, 10 and 20 respectively. After preparation, the solubilited forms were then stored at temperature of 25O and 45OC, and observed if there were any solubilization occurred. The results have showed that it needs an optimum length of ethyleneoxyde to have better solubilization; at certain longer ethylenoxyde the longer the length of lipophilic chain, the more solubilization would be, therefore, unsaturated hydrocarbon chain caused diminution of solubilization; whatever the surfactant used as an agent of solubilization, storage at a higher room temperature would facilitate the solubilization to occur.Key words : surfactant, solubilization